Kepemimpinan Kyai Dalam Memberdayakan Keagamaan Di Masyarakat (Studi Tokoh K.H. Achmad Muchtar Ghozali pengasuh Pesantren PPAI Darun Najah Desa Ngijo Kec. Karangploso Kab. Malang) - Cicik Rohmaniyah Salim (STAI Ma'had Aly Al-Hikam Malang, 2021)
The leadership of the Kyai is special because it is not yet known in depth by the society. A Kyai has a very important role in providing religious education to the society. The leadership of the Kyai has another feature, which is to make the society more easily influenced and obedient to the matters conveyed by the Kyai. Likewise with the leadership of KH. Ahmad Muchtar Ghozali. He has an important role in providing Islamic religious education to the society. The purpose of this study is to describe and analyze the type of leadership KH. Ahmad Muchtar Ghozali, his efforts in empowering religion in society, as well as describing the implications of the leadership results of KH. Ahmad Muchtar Ghozali in empowering the society. The method used in this study is a qualitative method and the research approach used is descriptive qualitative with the type of life-history research. Data collection techniques through interviews, observation, and documentation study. The research instrument was the researcher. Checking the validity of the data using triangulation techniques, peer checking, and member checking. This research results indicates that: (1) the type of leadership KH. Ahmad Muchtar Ghozali is charismatic and democratic. (2) KH. Ahmad Muchtar Ghozali in empowering religion is by becoming a mosque stakeholder, mubaligh (preaching), teaching, being active in ORMAS activities (society organizations) to establishing a Islamic boarding school and formal education, (3) the implication of KH leadership. Ahmad Muchtar Ghozali in empowering religion in society is the creation of a society that upholds Islamic values and is able to produce the younger generation to become an ulama’ (scholar).